A prática do canto lírico na Escola de Música da Universidade Federal do Rio Grande do Norte - Simas, Maria Thereza Pinto (2011)
The monograph in question tried to know the practice of singing songs at the School of Music of the Federal University of Rio Grande do Norte - EMUFRN. The practice of the song lyric requires years of training, because it is a hard working, where it is possible to wish immediate results. It is the teacher of singing guide the student in search not only of vocal techniques, but also the knowledge of his own body. The methods used by the teachers, the projects available in the area and the prospects in the labor market, guided the interviews conducted. Was made use of an open interview, structured so that the interviewee had freedom to talk about the proposed theme. It was approached the historical context in which is inserted the song lyric, its origin, the rapprochement with the opera and its composers. He was also the presence of the song lyric in Brazil and the description of the techniques used by the teachers in their classrooms, such as the importance of a correct breathing is the proper use of the diaphragm in the whole process that involves the training until the issue of singing voice. The discussion of the results collected was made through excerpts from transcripts of the teachers interviewed, interspersed with the opinion anonymously of the students who participated, with suggestions for improvement and also highlighting the positive aspects of didactics by singing teachers.